Prediction of springback in the forming of advanced high strength steel: simulation and experimental study - Mohamad Noor, Noraishah (2011)
Dual Phase (DP) steel is categorized as advanced high-strength steels (AHSS) which has tensile strengths ranging from 500 to 800 MPa. DP steel is gaining popularity in automotive applications. It has higher formability than HSLA grades with similar initial yield strengths, but has much higher final part strength. With proper design strategy, Dual Phase (DP) steels offers a great advantage in terms of body weight reduction and crash performance. One of the major constraints in forming AHSS is the occurrence of high springback caused by elastic relaxation after loading, which causes ill-fitting in part assembly and geometric deviation of the intended design. This research focused on finite element (FE) simulation of the sheet forming of dual phase steel and the springback prediction. If springback could be accurately predicted, the forming die could be correctly designed to compensate springback. The material used in this study was DOCOL 800 DP manufactured by SSAB- Sweden with ultimate tensile strength of 870 MPa and thickness of 0.72mm. The plastic behavior of DP800 was presented by exponential based constitutive equation known as isotropic hardening. From tensile test, strain hardening value (n) was 0.308 and strength coefficient (K) was 1319.165 MP. The FE simulations were conducted for tensile test, U-channel forming and springback simulation. These simulations were carried out by using general purpose transient dynamic FE code Lsdyna. The tensile test simulation result indicated the isotropic hardening material model was suitable for DP800 behavior with standard deviation value 62.45 MPa between simulation and experiment. Meanwhile, the springback simulation using U-channel represented the deviation for BHF 10kN, 20kN, 30kN and 97kN were 0.019, 0.071, 0.341 and 0.231. Overall, the result of 20KN BHF applied indicated the minimum springback in the forming of DP800.